Pemberdayaan Masyarakat Melalui Budidaya Tanaman Herbal di Dusun Sempon Kulon, Gunung Kidul - Ahyar, Mufahras; Maharani, Nurcahya; Khafiyya, Merwindha; Alhamndi, Suryo Achmad; Wahyuni, Sri; Febriani, Wanda; Ramadhan, Fawaz Shauma; Fadhil, Wildan Aulia; Krisnawan, Muhammad Fahri; Rohmansyah , Rohmansyah (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This community service focuses on empowering the community of Sempon Hamlet, Dadapayu Village, Gunung Kidul Regency, through the utilization of Family Medicinal Plants (TOGA) with polybag planting media. Located in a mountainous area, Sempon Hamlet has the potential of natural resources in the form of various types of medicinal plants that have not been optimally utilized by the community. Limited access to modern health services and challenging geographical conditions are the main background for the implementation of this program. The main objective of this service is to increase community knowledge and awareness in maintaining health through the utilization of local potential. This program is implemented through three main stages, namely observation, socialization, and planting practices. The results of this activity show a significant increase in community knowledge and skills related to TOGA. The community showed high enthusiasm in participating in the activities, reflected in the increased understanding of the benefits of medicinal plants and farming skills. The use of polybags as a planting medium has proven effective in overcoming land limitations, allowing people to plant TOGA in their yards. In addition, this program also increases community awareness of the importance of preventive health and the utilization of local natural resources. The follow-up plan of this service includes evaluation of the long-term impact of the program, development of TOGA processed products with economic value, TOGA product marketing training, formation of TOGA farmer groups, detailed documentation of TOGA cultivation and processing processes, cooperation with related parties, and utilization of technology for information dissemination. With the right follow-up steps, this program is expected to provide a greater and sustainable impact on the community in Sempon Hamlet.